42 rules for 24-hour success on LinkedIn [electronic resource] - Muccio, Chris; Burns, David; Murrah, Peggy (SuperStar Press, 2009)
Do you know how to use LinedIn to achieve your business goals? There are millions of registered users on LinkedIn. Relatively few of them seem to have any real understanding of how to effectively use LinkedIn. With registered users of LinkedIn projected to grow to 70 million by the end of 2009, business professionals are searching for ways to leverage this new communication meduim. Although social networking is exploding, there are very few resources that teach what users are craving, solutions to increase their desired business success.